If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 8) = 11 Reorder the terms: 5(8 + x) = 11 (8 * 5 + x * 5) = 11 (40 + 5x) = 11 Solving 40 + 5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 5x = 11 + -40 Combine like terms: 40 + -40 = 0 0 + 5x = 11 + -40 5x = 11 + -40 Combine like terms: 11 + -40 = -29 5x = -29 Divide each side by '5'. x = -5.8 Simplifying x = -5.8
| -6(5-r)=-60 | | 6y=-5y^3-17y^2 | | 10x-177=95-7x | | 3x-40=2x+10 | | 4x-144=128-12x | | ln(8)=ln(4)+ln(x) | | 10(0.4+0.5g)=4g | | 0.02x+0.01(70)=0.02(70) | | x-99=62-6x | | -4(2y+6)=16 | | -1.4(5-x)+2.5(2+x)=-3.6+x | | -2u+14+3=8u+27 | | 3a+3=3 | | 7y+5+3y+4+14y-15=180 | | 3x-86=49-6x | | 7n-8=-16+3n | | 5x(x+7)=20 | | -3(x-2)+4(2x+5)=10x-(5x-23) | | x+7+z=-11 | | -20-7x=16+9x | | 90x=585 | | 36-14x=8 | | 5x=4+-4+5x | | 20(5)=20q+5 | | 8n-2=19+5n | | 6t-12-(3t-3)=-19 | | 2(x-1)+3(x+2)=5x+4 | | 2(2x)+47=2(2x)+47 | | -40+3x=10+2x | | 6x-12=5x+17 | | 6(y-24)-6y=0 | | -40+3x=2x |